For Never Was a Mazier Mystery Than That of Phoneme and Its History - A. V. Ivanov (Научный диалог, 2022)
The aim of the research is to study and systematize etymological, historical-linguistic and historiographic information about the terms fonema / phoneme / Phonem based on the results of the analysis of Russian, English and German theoretical and lexicographic sources published in the 19th—20th centuries. Sources in French are used where necessary. The methods of historical-linguistic, historiographical, definitional, etymological, semantic and lexicographical analysis are used in the study. It has been established that in the ancient Greek language, which is the source of the origin of the word φώνημα, the latter was used in two general meanings: (1) ‘voice, sound’, (2) ‘word, speech’. In the second half of the 19th century, in the new European languages, the word underwent adaptation, subsequent semantic rethinking and acquired a terminological status. The term phonème was first used by the French amateur linguist A. Dufriche-Desgenettes in 1861 in the generalized phonetic meaning ‘sound’. In the phonological sense, this term is found by F. de Saussure in 1879. The term fonema (phoneme) was introduced into Russian linguistic terminology in 1880 by N. V. Krushevsky and, starting from 1881, was widely used in the works of I. A. Baudouin de Courtenay, V. M. Dobrovsky and others. The first use of the English term phoneme in the meaning of ‘sound’ should presumably be attributed to 1914, and not to 1894, as evidenced by English lexicographical sources. In a highly specialized (phonological) sense, the term was fixed in English linguistic terminology already in 1919, when the corresponding word usage was recorded in the work of G. Perera and D. Jones. In the vocabulary of the German language, the term Phonem in the meaning of ‘sound’ appeared in 1855 thanks to the Bulgarian philosopher P. Beron. In a similar sense, the desired term is found in 1875 by E. Boehmer. In its phonological meaning, the German term Phonem occurs for the first time in the works of I. A. Baudouin de Courtenay in 1895.